ANALISA PENGARUH KARAKTERISTIK KEKUATAN PERSAINGAN PORTER TERHADAP KINERJA SEKOLAH DENGAN PENDEKATAN BALANCED SCORECARD - Robertus Sidhartawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2011)
The Schools have to anticipate the influence of external environments. The external environment analysis consist of the macro and micro analysis. The micro analysis used Porter`s five force model of competitiveness consist of threat of new entrans, the bargaining power of supplier, the bargaining power of customer, threat of substitutes schools and rivalry among existing schools. The purpose of this study was to examine the Porter`s five force model of competitiveness on organizational performance of school in balanced scorecard approach. Data for this study were collected from middle schools using a self-administered survey questionnaire. Hypothesis test showed that threat of new entrans, the bargaining power of supplier, the bargaining power of customer, threat of substitutes schools and rivalry among existing schools examined had a significant impact on school performance in balanced scorecard approach. but partially only threat of new entrans, the bargaining power of supplier, and rivalry among existing schools are significantly influence on schools performance in balanced scorecard approach. but for the bargaining power of customers, and the threat of substitutes schools aren’t significantly influence on schools performance in balanced scorecard approach. Keywords: external environment, micro environment analysis, Porter`s five force model of competitiveness, performance, balanced scorecard